Household Equivalence Scales: Theory versus Policy? - Nelson, Julie A. (Journal of Labor Economics, 1993)
Researchers agree that household equivalence scales are intended to measure the variation in income needed to bring households of different composition to the same welfare level. Researchers do not agree, however, about how the term "household welfare" is to be defined. This article traces the historical and philosophical development of three distinct definitions. When the conceptual bases of several popular methods for the estimation of equivalence scales are explored, it becomes clear that advances in theoretical rigor have not always worked to bring the literature closer to answering questions of policy concern.